Le sol : enquête sur les mécanismes de (non) émergence d’un problème public environnemental - Juliette Fournil; Juliette Kon Kam King; Céline Granjou; Lauric Cécillon (VertigO)
While soil is crucial to human activity and ecosystem functioning, there is no policy specifically focused on soil conservation. We argue that the difficulties to implement soil conservation policies are not merely due to the invisibility of the underground world and the threats on its life and functioning. Instead, we need to unpack how soil has been set onto political agenda as an environmental issue, and to analyze the specific repertoires and language in which soil conservation is articulated. Drawing on a multidisciplinary approach including social sciences and soil sciences, we accounted for the logics of requalification of soil as environmental issue at play since the mid 2000s and for their relationships with the dominant agricultural qualification of soil as a material substrate for fertilization and agronomic productivity. Drawing on an in-depth qualitative investigation in France, including documentary exploitation and interviews, we identified two distinct logics of environmental requalification of soil, respectively in terms of endangered biodiversity and threatened soils in need of conserving, and in terms of soil functions and soil ecosystem services in need of conserving and securing. We finally discuss how those logics tend to unsettle agricultural logics and power relations or to comply with them.